A Tunable Synchronous Pulsed Dual-Wavelength Laser Based on the Nd:YVO4/Nd:GdVO4 Combined Crystals Pair - Yizhi Ke; Miao Hu; Mengmeng Xu; Mengying Xia; Huimin Zhou; Qiliang Li; Xuefang Zhou; Guowei Yang; Meihua Bi (IEEE Photonics Journal)
A tunable pulsed dual-wavelength laser is presented based on an Nd:YVO4/Nd:GdVO4 combined crystals pair as amplifying medium. By employing pulse width adjustment of an 808 nm laser diode pumping, and a Cr4+:YAG crystal for Q-switching, synchronized dual-wavelength laser pulses were obtained at 1063 nm and 1064 nm. Time jitter between the two wavelength pulses is reduced to about 10% of the laser pulse duration. Adjusting the pump beam operation parameters and tuning the crystals pair steady-state temperature between 10 °C and 50 °C, the frequency separation between the dual-wavelength laser pulses gradually decreases from 344.11 GHz to 305.99 GHz. The relative peak powers and the pulses time synchronization remain stable during their frequency separation tuning.